Budaya Organisasi Dhammasekha Saddhapala Jaya sebagai Lembaga Pendidikan Nonformal Agama Buddha - Dewi, Metta Puspita (Center of Language and Cultural Studies, 2021)
Dhammasekha Saddhapala Jaya is a non-formal Buddhist religious education route organized by a Buddhist education foundation. Dhammasekha Saddhapala Jaya aims at instilling faith, morality and improving the quality of Buddhist human resources. An organizational culture that develops in accordance with Buddhist values ​​includes belief in Buddha's teachings (saddha), morality (sila), willingness (dana), self-sacrifice (paricagga), enthusiasm (viriya), loving-kindness (metta), and respect for all the citizens of Dhammasekha. Spiritual guidance for students is balanced with skills, arts, and culture. Dhammasekha provides support for teachers to obtain education and training to improve teacher professionalism. Dhammasekha maintains several quality components, including focusing on customers, teamwork, education, and continuous improvement to improve the quality of Dhammasekha Saddhapala Jaya.